Hand eczema prevalence among healthcare workers during COVID-19 pandemic – a systematic review - Sroczyńska, Monika; Luchowska, Anna; Żaczek, Aleksandra (Journal of Education, Health and Sport, 2022)
Introduction The globe is currently experiencing a new pandemic due to the introduction of the SARS-CoV-2 strain of the human coronavirus. The virus infects people and causes COVID-19, a lung condition that can be fatal in susceptible people and is characterized by fever, pneumonia, and shortness of breath. The prevalence of hand eczema among healthcare professionals working in COVID-19 units has grown, and it has been linked to increased hand sanitation habits. Aim of the study The purpose of the study was to examine the prevalence of hand eczema as a consequence of more intensive hand hygiene among healthcare workers during COVID-19 pandemic. Materials and methods A search was conducted using PubMed and Google Scholar databases. Articles were searched in English using the following key words: hand eczema; hand dermatitis; atopic dermatitis; COVID-19; SARS-CoV-2. Results Healthcare workers developed hand eczema more frequently in COVID-19 outbreak. The risk of hand eczema was raised by frequent use of hand hygiene products, alcohol-based hand sanitizers, wearing gloves, previous atopic dermatitis history and female sex gender. Due to excessive hand hygiene the natural skin barrier function was impaired, leading to hand eczema. The use of preventive skincare products can lower the risk of hand eczema development. Conclusion Findings demonstrated positive correlation between hand eczema prevalence among healthcare professionals and COVID-19 pandemic. Hand washing and the use of disinfectants disrupt the natural skin barrier function, leading to allergic and irritating hand eczema. In order to continue practicing hand hygiene during the continuing pandemic, proper prevention strategies and education should be implemented.